Transplantation tolerance-where do we stand? - Waldmann, H (1999)
Our understanding of tolerance mechanisms has progressed to the point that tolerance-induction protocols are being tested in humans for organ transplantation. However, a range of scientific, ethical, logistic and commercial issues have arisen, and must be resolved before tolerance induction for human allograft patients can become a reality.